White etching matter promoted by intergranular embrittlement. (15th March 2017) - Paladugu, Mohanchand; Scott Hyde, R.
Abstract: To determine the role of brittleness in producing "white etching matter, " rolling elements were intentionally case-carburize heat treated to produce an embrittled case. The intergranular embrittlement was confirmed by characterizing the fracture surfaces of the steel. Post rolling contact fatigue investigations showed subsurface cracks, forming preferentially along the grain boundaries, and white etching matter was determined to be present along these intergranular cracks. The white etching matter was characterized by electron microscopy. These results provide novel insights into cause-effect relationships and evolution mechanisms associated with white etching matter. Graphical abstract: